An empirical analysis of Sustainable Earth-Battery. (September 2021) - Borno, Md. Samiul Islam; Sayeduzzaman, Md.; Elme, Khan Md.; Islam, Md. Hasibul; Rahman, Md. Abdur
Abstract: The renewable energy and alternative power sectors are rising with less global warming, improved public health, inexhaustible electricity, and affordable energy prices day by day. A Sustainable Earth-Battery can be used as an alternative power source as there is no need for an external power to charge the Earth-Battery because it can get charged naturally in the presence of water. This paper aims to show how electricity is generated from the soil and to operate small-scale powered devices. Various soil samples, influential reactors, and electrodes were examined for the entire potential difference and electron flow. After experimentation, it has been shown that Carbon (C6 ) and Aluminum (Al13 ) can provide feasible power as an electrode. In a series–parallel relationship between soil cells in the presence of water and energy generation systems through the soil, natural water, filtered and modified soil has been used to achieve maximum efficiency. So, it is also called the water-activated battery, and there is no such thing as a toxic substance that can affect the environment. As a result, it can also be considered a clean energy source. The priority was to use raw materials concerning cost and availability. This paper explains the design, operations, characteristics, and best possible way of soil powered electricity generation system.